Distal radius nonunion after epiphyseal plate fracture in a 15 years old young rider: Distal radius nonunion in adolescent - Pedrazzini, Alessio; Bastia, Paolo; Bertoni, Nicola; Pedrabissi, Bianca; Simo, Henry Claudel Yewo; Medina, Vanni; Ceccarelli, Francesco; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: Radius and ulna fractures are the most common long bone fractures in children and adolescents. The majority of these injuries involve the distal metaphyseal portion of the radius associated or not to physeal plate injuries. Because of the high remodelling potential of the distal radius in growing children most injuries heal without complication after closed reduction and immobilization in a long arm cast. Nonunions of closed distal radius fracture are an extremely rare occurrence especially in paediatric population. Methods: In this report, we describe a rare case of distal radius fracture nonunion in a 15-years old male rider treated conservatively with cast immobilization. Eight months later he underwent surgical closed reduction and fixation with kirschner wire and cannulated screw. Results: Follow-up at 2 years showed satisfying radiological and functional outcomes. The patient ultimately returned to ride 3 months following surgery. Conclusions: Nonunion is rarely seen in distal radius fractures in healthy children and adolescents, and there are few studies in the literature. Treatment of the nonunion must be individualized and the results are not entirely predictable.